A Long View of Resilience in the Chengdu Plain, China. Issue 2 (May 2019) - Whiting, Susan H.; Abramson, Daniel; Yuan, Shang; Harrell, Stevan
Abstract : The Chengdu Plain is an agroecosystem that depends on the Dujiangyan (Capital River Weir) for its functioning. This system has been sustained at high levels of productivity for more than two thousand years, experiencing only a few disturbances that have disrupted its functioning. Integrating field and documentary research on ecological, market, and governance factors, this article discusses the remarkable resilience of this system from the late Qing to the present and identifies current threats to its resilience. When the ecology consists of patchy and diverse landscapes, markets allow for adaptation through exchange, and governance includes cross-cutting sources of authority and flexible property regimes, the ecosystem is more resilient—that is, better able to withstand disturbances and maintain its basic functions.